UNSUR KEBARUAN ATAS KARYA DESAIN INDUSTRI KEMASAN MAKANAN (STUDI PUTUSAN PENGADILAN NIAGA NOMOR 16/PDT.SUS.DESAIN INDUSTRI/2020/PN.NIAGA.JKT.PST JO PUTUSAN KASASI NOMOR 162 K/PDT.SUS-HKI/2021) - Rahmawati, Rista Anggun; Kerti, N.G.N Renti Maharaini (Tribuere, 2023)
Industrial designs in registration must meet the requirements for elements of novelty, which are not similar or the same as previous designs. Industrial Design Regulations already exist, but there are many disputes resulting in problems being committed by Industrial Design Rights Holders and Industrial Design Rights Violators. Referring to the case where the food packaging design owned by Ruben Samuel Onsu does not have an element of novelty. Inside the packaging there is a resemblance to the food box packaging owned by PT. Ayam Geprek Benny Sujono. In this case, there is a problem where the criteria for novelty and the legal considerations of the commercial and cassation court regarding the cancellation of the registration of the food box packaging industrial design. The research method in this case is the type of research used juridical-normative. The nature of the research is descriptive. The data used is secondary as well as data collection by way of literature study. Data analysis uses qualitative and drawing conclusions on this problem using deductive logic. In cases where violations are found, there is no element of novelty as referred to in the statutory rules and there is no bad faith at the time of registration, so that becomes an important factor for the party objecting. Parties who have objections can submit an annulment of registration in the commercial court carried out by parties who have an interest.